Sleeping, Death and Life after Death: An Inferential Comparative Study - Hakeem Adeyinka, Kolawole; Abeebllahi Obalowu, Issah (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
Abstrac This paper presents an inferential comparative analysis of the relationship between sleep, death, and life after death. The depiction of sleep and death in the Qur’an and Sunnah is highlighted by delving into the position of the soul and its experience in both circumstances to repudiate the doubt about the life of the body and soul during the period between death and resurrection. In addition to the Qur’anic and Hadith texts that establish this fact, clear, rational evidence is also provided in this paper to bolster the claim. The study uses a qualitative method, relying on analytical, descriptive, comparative, and critical analyses to explore some verses of the Qur’an and hadiths of the Prophet (saw) to present its arguments. Likewise, the daily empirical human experience during their sleep and while awaking is also presented by highlighting the similarities between sleep and death on the one hand and what happens to a person during sleep and after death on the other hand, to prove the possibility of the existence of life in the grave. So, the research establishes the reality of the punishment and enjoyment in the grave -the period between death and resurrection- by inference the relationship between sleep and death on one side, and the connection between the experience of the soul and body in the dream and what the soul and body encounter in the grave after the Soul is restored to the body again on another side.